Identification and Efectiveness of Halal Tourism Laws in Indonesia - Cucu Susilawati (Muhammadiyah University Press, 2023)
This research is an effort to support the development of halal tourism in Indonesia. Indonesia has two crucial points in halal tourism: having a variety of attractive halal tourist destinations and a sizeable Muslim community. However, Indonesia still needs to improve compared to other countries. The authors found that the main factor was improper, clear, and comprehensive regulations. This type of research is juridical–empirical research. The research data was obtained through indirect interviews and secondary data. The stages are preparation, planning, implementation, and formulation of research results. The result is that the regulation of halal tourism in Indonesia is an unwritten law, namely the DSN – MUI Fatwa Number 108/DSN-MUI/X/2016, concerning Tourism Implementation Based on Sharia Principles. Another written regulation used as a guideline for halal tourism is Law Number 33 of 2014 concerning Guaranteed Halal Products. However, Law Number 33 of 2014 is impractical for implementing halal tourism in Indonesia. In conclusion, the Indonesian government must make a law that explicitly regulates halal tourism. The advice is the DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 concerning implementing Tourism Based on Sharia Principles can be transformed into positive law.